IDENTIFYING COMMON CONTRASTIVE ERRORS IN ENGLISH GRAMMAR MADE BY INDONESIAN EFL LEARNERS: CAUSES AND SOLUTION - Sabrina, Azra Batrisyia; Sitanggang, Cansa Namira; Salmanda, Dandi; Fadhila, Fadhila; Fadlan, Fadlan; Mashalan, Fahima; Purba, Kezia Nur Elizanti; Khairunnisa, Khairunnisa; Fitria, Lailatul; Fadhila, Nurul; Batubara, Putri Fadila; Aulia, Sirrul; Ismahani, Siti (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study identifies common contrastive errors in English grammar made by Indonesian EFL learners, along with their causes and solutions. Such errors often arise from structural differences between the learner's first language (L1) and English (L2), potentially leading to misunderstandings. Using a descriptive qualitative research design, data were collected from eleven undergraduate students in the English Education program at Universitas Islam Negeri Sumatera Utara. Data collection methods included grammar tests and surveys to explore the underlying causes of errors. Analysis revealed that common errors included tense usage, subject-verb agreement, article usage, and preposition errors. These mistakes are attributed to language transfer, interlanguage phenomena, and a lack of understanding of English structures. The study recommends teaching strategies such as drilling activities, corrective feedback, context-based learning, and comparative grammar analysis to mitigate these errors. By implementing these approaches, it is hoped that learners will enhance their understanding and application of English grammar more effectively, ultimately improving their communication skills in English.